2000
DOI: 10.1177/002204260003000204
|View full text |Cite
|
Sign up to set email alerts
|

Injecting Drug Use and HIV in Moscow: Results of a Survey

Abstract: Russia has experienced a large increase in injecting drug use since the col/apse of the Soviet Union. Injecting drug use is presently attributed with up to 90 perccent of newly acquired HIV. Peer educators of an outreach program conducted a survey of injecting drug users (IDUs) in Moscow. The survey was supplemented by qualitative field notes. Due to differences in settings and methods, the hospital and street survey resufts are presented separately. A total of 298 hospital and 126 street surveys were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In Warsaw 31.3% of users shared needle in the previous 30 days between 1995 and 1999, while in 2000 the figure was 16.9% (European Monitoring Centre for Drugs and Drug Addiction 2002). Studies from the late 1990s found that in Saint Petersburg 41% of IDUs, and in Moscow, between 40-75% were sharing needles (Somlai et al 2002;Reilley et al 2000;Gore-Felton et al 2003). A study among IDUs in Hungary found that 25% of participants reported receptive syringe sharing and 18% distributive syringe sharing, and rates of sharing cookers and cotton were 55% (Gyarmathy & Neaigus 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Warsaw 31.3% of users shared needle in the previous 30 days between 1995 and 1999, while in 2000 the figure was 16.9% (European Monitoring Centre for Drugs and Drug Addiction 2002). Studies from the late 1990s found that in Saint Petersburg 41% of IDUs, and in Moscow, between 40-75% were sharing needles (Somlai et al 2002;Reilley et al 2000;Gore-Felton et al 2003). A study among IDUs in Hungary found that 25% of participants reported receptive syringe sharing and 18% distributive syringe sharing, and rates of sharing cookers and cotton were 55% (Gyarmathy & Neaigus 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Moldova, where most HIV infections are associated with drug use, over 80% of IDUs share needles, primarily to show trust towards their friends 16 . In a Moscow sample, 75% of drug users shared injection equipment in the past month and almost half shared or re-used equipment at the time of their last injection 43 . Only 10% of IDUs cleaned needles prior to re-use with bleach or by boiling, while 76% attempted to clean their syringes but in ineffective ways.…”
Section: Risk Behaviour Among Injection Drug Usersmentioning
confidence: 99%
“…In one 10‐site study with five sites in Russia and five elsewhere in eastern Europe, 46% of IDUs reported chornaya use, but the percentages ranged from 6% in St Petersburg to 84% in Rostov‐na‐Donu and 97% in Poltava, Ukraine [13]. In Moscow, chornaya was used by 36% of respondents interviewed in 1997 and 1998 [14]. Our own fieldwork has found chornaya the predominant injected drug in five of 11 Russian cities we visited.…”
Section: Introductionmentioning
confidence: 99%
“…One theory implicates the common use of contaminated equipment for the storage, distribution, apportioning or injection of the drug. Another theory is based on reports that in some cases, human blood may be added to the drug solution during its manufacture as a cleansing or filtering agent [10,11,14–16]. If true, the widespread occurrence of either practice could contaminate the drugs themselves with HIV‐1, promoting the epidemic spread of the virus among IDUs [17].…”
Section: Introductionmentioning
confidence: 99%